PENGARUH PERLAKUAN DELIGNIFIKASI DENGAN LARUTAN NAOH DAN KONSENTRASI SUBSTRAT JERAMI PADI TERHADAP PRODUKSI ENZIM SELULASE DARI ASPERGILLUS NIGER NRRL A-II, 264 - GUNAM, IDA BAGUS WAYAN; BUDA, KETUT; GUNA , I MADE YOGA SEMARA (Jurnal Biologi Udayana, 2010)
his research was done in order to utilize agricultural waste (rice straw) as substrate to produce crude cellulase enzyme from Aspergillus niger. This research was conducted in two stages; the first stage was determination of the initial pH and fermentation time by pH treatment (5, 6 and 7) and fermentation time (7, 9 and 11 days). The second stage was determination of concentration of NaOH treatment and concentration of substrate, namely: concentrations of NaOH (2, 4 and 6%) and concentrations of substrate (1, 2 and 3% (w/v)). The results showed that the fermentation time of 9 days with the initial pH 6.0 was the optimal condition for production of crude cellulase enzyme from A. niger with rice straw as a substrate. The highest enzyme activity derived from interaction of delignification treatment with NaOH concentration of 6% and 2% rice straw substrate which produces endoglukanase enzyme activity (0.037 units/ml), filter paperase activity (0.033 units/ml), soluble protein (0.362 mg/ml), and specific activity of filter paperase (0.123 units/mg).
Keywords: Rice straw; lignocellulose; cellulase; Aspergillus niger